The Effect of Financial Knowledge, Financial Literacy, and Financial Capability on MSME Performance - Maulinda Putri Riyadi; Vidi Hadyarti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
MSMEs frequently face development challenges due to a lack of financial expertise. Thus, the purpose of this study is to determine how much financial literacy, financial knowledge, and financial competence impact MSMEs' performance in Sampang Regency. The important of information and skills for corporate success is emphasized in this study. 55 MSMEs made up the sample set, which was selected using a purposive sampling strategy and a quantitative approach. Questionnaires were distributed in October 2024, and SPSS was used to analyze the data. According to the study's findings, MSME performance is positively and significantly impacted by financial knowledge, financial literacy, and financial competence. This result highlights how crucial training and capacity building initiatives are for MSME actors looking to advance their financial literacy. This study creates avenues for future research to delve deeper into the processes that connect MSME success to knowledge, literacy, and financial capacities, as well as other factors that impact MSME performance.